Is there an informal employment wage penalty? Evidence from South Africa - Eliane Badaoui; Eric Strobl; Frank A. Walsh (Institute for the Study of Labor (IZA), 2007)
We estimate the wage penalty associated with working in the South African informal sector. To this end we use a rich data set on non-self employed males that allows one to accurately distinguish workers employed in the informal sector from those employed in the formal sector and link individuals over time. Implementing various econometric approaches we find that there is a gross wage penalty of a little over 18 per cent for working in the informal sector. However, once we reduce our sample to a group for which we can reasonably calculate earnings net of taxes and control for time invariant unobservables the wage penalty disappears.
Keywords: J31; 330; Informal sector; wage penalty; South Africa; Lohnstruktur; Informeller Sektor; Südafrika